Evaluation of Processing Conditions on the γ′ Morphology of an Oxide Dispersion Strengthened Ni‐Based Superalloy. Issue 3 (30th July 2020) - Aghamiri, S. M. S.; Linye, Z.; Ukai, S.; Oono, N.; Shahverdi, H. R.; Soltanieh, M.
Abstract : Herein, the evolution of the microstructure of a newly developed oxide dispersion strengthened (ODS) Ni‐based superalloy with emphasis on γ′ morphology during different processing conditions is investigated. X‐ray analysis of severely deformed mechanically alloyed (MAed) powders shows that the as‐milled nano‐sized crystallite size increases with annealing associated with the sharp drop of dislocation density. At the same time, by annealing MAed powders γ′ precipitates above 300 °C, and depending on the aging treatment regime, Vickers microhardness changes mainly due to γ′ distribution and dislocation release. The thorough evaluation of γ′ morphology in the microscale shows that in contrast to the spherical shape of γ′, after heat treatment of solutionized MAed ODS superalloy, irregular‐shaped γ′ exist in the MAed ODS superalloy due to severe plastic deformation during mechanical alloying. However, a unique nanostructured lamellar morphology forms in the γ′ precipitates with different lamellae directions. This structure is stable in all subsequent processing steps with γ′ lamellae of ( 01 1 ¯ ) planes and intervals of 20–30 nm. The scanning transmission electron microscopy (STEM)–high‐angle annular dark‐field (HAADF) composition analysis clarifies that the nanostructured lamellar morphology shows no partitioning of alloying elements, and its origin may be attributed to the formation of antiphase domain boundaries. Abstract : The evolution of the microstructure of a new oxide dispersion strengthened (ODS) Ni‐based γ–γ′ dual‐phase superalloy is investigated during different processing conditions of mechanical alloying, hot extrusion and zone annealing, and aging treatments. A unique nanostructured lamellar morphology forms in γ′ precipitates in all processing steps with γ′ lamellae of ( 01 1 ¯ ) planes and intervals of 20–30 nm.